2020
DOI: 10.1039/c9nr08542d
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress and advances in the environmental applications of MXene related materials

Abstract: MXenes are a new type of two-dimensional (2D) transition metal carbide or carbonitride material with a 2D structure similar to graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(91 citation statements)
references
References 176 publications
0
91
0
Order By: Relevance
“…There are numerous published reviews in the fields of MXenes for energy, catalysis, and environmental remediation [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, the reviews on the mechanical properties of self-standing MXenes are not yet reported [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous published reviews in the fields of MXenes for energy, catalysis, and environmental remediation [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, the reviews on the mechanical properties of self-standing MXenes are not yet reported [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2D structure and high electronic conductivity of MXenes make people naturally recall the star 2D material, graphene. [64] Thus far, the progress on applying MXenes for photocatalysis is mainly concentrated on using MXenes as electron acceptors to promote the separation of charge carriers in semiconductors, [16,24,25,[45][46][47][48] as graphene has done over the past decade. [65][66][67] As such, we spontaneously encounter the questions: what are the unique properties of MXenes and what can MXenes bring to us for photocatalytic applications?…”
Section: What Can Mxenes Bring For Photocatalysis?mentioning
confidence: 99%
“…Thus far, various semiconductors/ MXenes composites have been constructed and utilized for a broad spectrum of photocatalytic applications, such as environmental remediation, water splitting for hydrogen evolution, CO 2 reduction, and nitrogen photofixation ( Figure 2). [16,[24][25][45][46][47][48] There have been some reviews recapping recent advances in using MXenes-based composites for photocatalytic applications. [16,20,24,25,[45][46][47][48][49] From these previous reviews, we can acknowledge that MXenes have been quickly becoming a research hotspot for constructing composites for photocatalysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two-dimensional (2D) transition metal carbides, nitrides, and carbonitrides (referred to as MXenes) have emerged (8,9) as promising nanoscale electronic materials with good electrochemical stability. They have also been reported as promising templates for the synthesis of functional micro/nano-structured materials such as transition metal oxides (TMOs), alkali-metal titanates, and their hybrids (10,11).…”
Section: Introductionmentioning
confidence: 99%